2014
DOI: 10.1155/2014/315952
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Microsurgery of Vestibular Schwannoma

Abstract: Background. The aim of this study was to analyze complications of vestibular schwannoma (VS) microsurgery. Material and Methods. A retrospective study was performed in 333 patients with unilateral vestibular schwannoma indicated for surgical treatment between January 1997 and December 2012. Postoperative complications were assessed immediately after VS surgery as well as during outpatient followup. Results. In all 333 patients microsurgical vestibular schwannoma (Koos grade 1: 12, grade 2: 34, grade 3: 62, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 70 publications
4
57
1
1
Order By: Relevance
“…Minovi et al [18] also reported on one case (1.1%) of lethal PE after DVT in a series of 89 AN patients operated on via MFA. There is a comparable rate of PE in further series with mixed approaches of 0.2%-1.1% [14,[19][20][21][25][26][27] .…”
Section: Deep Venous Thrombosismentioning
confidence: 73%
See 1 more Smart Citation
“…Minovi et al [18] also reported on one case (1.1%) of lethal PE after DVT in a series of 89 AN patients operated on via MFA. There is a comparable rate of PE in further series with mixed approaches of 0.2%-1.1% [14,[19][20][21][25][26][27] .…”
Section: Deep Venous Thrombosismentioning
confidence: 73%
“…Despite this low number, intracranial bleedings are the most common cause of death after AN surgery as reported for all approaches and all tumor sizes [5,14,19] . These bleedings are often caused by direct damage to vessels in the field of surgery.…”
Section: Hemorrhagementioning
confidence: 95%
“…Mortality and morbidity have been reduced grossly in the recent years. CSF leakage, meningitis, postoperative headache, intraoperative vascular accidents, cranial nerve injuries are the main complications [14]. Availability of ultrasonic aspirators, shavers, and fiber lasers make the total excision more promising in reducing the morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, sophisticated tools are still lacking in developing couturiers due to limited resources. Most of the complications are the consequences of the inadequate surgical maneuvers ascertaining the vital structures complicated by the tumor [14]. Meticulous surgical excision and postoperative care are always mandatory for gross total removal without complications (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 3 patients reported a slight improvement in symptoms specifically related to vestibular dysfunction. Similarly, trigeminal neuropathy often goes unreported in the literature [32,34,35], with V2 and V3 representing the most frequently affected braches. In our study 4 patients (17.39%) developed postoperative facial numbness, with a resolution of symptoms occurring in all but 1 within the 1-month follow-up.…”
Section: Discussionmentioning
confidence: 99%